Pengetahuan dan Perilaku Pencegahan terjadinya Diabetes Melitus Tipe II pada Usia Remaja - Nurul Paramitha; Jaka Pradika; Syahid Amrullah; Suriadi (Jurnal Riset Keperawatan dan Kesehatan, 2026)
Background: Type II diabetes mellitus (T2DM) is a metabolic disorder characterized by hyperglycemia caused by impaired insulin secretion, insulin action, or both. The increasing prevalence of T2DM, including among adolescents, has become a major public health concern. Adolescents are particularly vulnerable to unhealthy lifestyles, while limited knowledge may hinder preventive behaviors. This study aimed to examine the relationship between knowledge and preventive behaviors toward T2DM among twelfth-grade students in Pontianak City, West Kalimantan Province. Methods: A correlational study with a cross-sectional design was conducted among 356 students selected through stratified random sampling from six senior high schools representing all districts of Pontianak City. Data were analyzed to determine the relationship between knowledge and T2DM preventive behaviors. Results: Most respondents were 17 years old (71.9%), female (51.4%), Muslim (84.8%), had no family history of diabetes (84.0%), had a normal body mass index (46.9%), and were non-smokers (82.6%). The majority had low knowledge regarding T2DM prevention (71.9%), whereas most demonstrated good preventive behaviors (89.9%). Statistical analysis revealed no significant relationship between knowledge and preventive behaviors toward T2DM (p = 0.758). Conclusion: Knowledge was not significantly associated with T2DM preventive behaviors among twelfth-grade adolescents in Pontianak City. These findings suggest that preventive behaviors may be influenced by factors beyond knowledge alone, highlighting the need for comprehensive health promotion strategies targeting adolescents.